Hi there!
Assuming "Find the product" means multiplying (4x-3) by (3x+8) and factor to it's simplest form the answer would be:
12x²+23x-24
The way you solve this is by using the distributive property of multiplication as shown below:
Start by multiplying -3 from (4x-3) by everything in (3x+8)
3x*(-3) = -9x
8*(-3) = -24
Once you've done that you then multiply everything 4x
4x*8 = 32x
4x*3x = 12x²
(Note: when multiplying two of the same variables like x it means you are multiplying x by itself which is the same as x²)
When you put all of this together it looks like this
12x²+32x-9x-24
from there we combine like terms
32x-9x = 23x
to get
12x²+23x-24
I hope this helps!
God bless,
ASIAX
Y = 20x
y • x = 180
180/x = y
180/x = 20x
180 = 20x^2
x^2 = 6
x = + or - 3
Therefore y must equal + or - 60.
To find the correct answer, you have to simplify the equation.
Multiply -1/2 by everything in the parenthesis.
3/4x - 3x - 1/2 - 3x. Combine like terms.
-21/4x - 1/2. Turn -21/4x into a mixed number.
-5 1/4x - 1/2.
Your answer is D
A^-b = 1/a^b
a^b / a^c = a^b-c
a^c / b^c =(a/b)^c